Legal Study of The Cancellation of Registration of Creations Constituting Investment in A Limited Liability Company Based on The Copyright Law and The Limited Liability Company Law - Riki Muhammad Firdaus; Nyulistiowati Suryanti; Muhamad Amirulloh (Faculty of Law, Universitas Pekalongan, 2025)
Capital invested in a company can be in the form of money or other forms, as regulated in Article 34 paragraph (1) of the Limited Liability Company Law No. 40 of 2007. Other forms (inbreng) include tangible and intangible assets that can be valued in money. Song Copyright is Intellectual Property and an intangible asset. This article describes the potential cancellation of copyright inbreng by a third party. The main issues are the status of shareholders whose copyright inbreng is revoked by the Directorate General of Intellectual Property (DJKI) and legal protection for the company as the recipient of the revoked copyright inbreng, reviewed under the Copyright Law and the Limited Liability Company Law. The research method used is a normative juridical approach, referring to Indonesian laws and regulations and societal norms. The research results are presented descriptively-analytically and analyzed qualitatively to provide a detailed and systematic overview. The conclusion shows that the inbreng agreement is null and void because the song copyright was proven unoriginal and copied from Jimmy Carter's work, the original singer of